"Ардын дүрслэлийн хэл-8" буюу тоонолжин зам - Д., Батжаргал (Mongolian Studies, 2023)
In this paper, I wrote more examples which was choose examples from the Inner Mongolian people's oral tradition. Students sent me interesting idioms which are said in different local area. The most of examples were not published and introduced to the masses, so I have chosen some of them and explained comparing with words of modern Mongolian. Also I made criticism in the words which are used wrong among the mass and social media. Therefore, I would like to say some warning to the journalists who do not pay special attention for their own language clear and are not innovative to combat for our Mongolian language safety.